(untitled) (International Journal of Environmental Sciences, 2025)
The environment crisis in India is nearing its breaking point, with industrialization, urbanization, logging, pollution, and global warming causing a serious deterioration of natural habitats and a decline in human health and biological diversity. The country is thus experiencing a rise in air and water pollution, depletion of groundwater sources, dwindling forest cover, and loss of wildlife habitats despite one of the most elaborate legal structures in the developing world regulating environmental protection. Such a paradox of the abundance of the laws regulating the environment and the simultaneous drastic ecological degradation of the environment reveals that the very essence of the issue is not the lack of a regulatory framework but the flaws of its implementation, accountability and coherence between different policies. The present paper examines critically the legislative lapses and policy vacuums impeding proper environmental governance in India. It looks at the legal framework that is in place, reasons out the gap between statutory clearance and the reality on the ground, reasons out the failure of the institution that are charged with the responsibility of regulation, and explores how the planning of development schemes have become so unsustainable as to erode all the environmental goals. This paper will argue the idea to go green through examples, case law, and empirical studies that depict a shift towards a sustainable model of governance which will be inclusive of environmental rights, decentralized planning, indigenous knowledge, climate justice, and scientific innovation. The proposed research has helped the researcher arrive at the conclusion that structural legal reforms, managing in the institution, involvement of communities and incorporation of environmental aspects in the mainstream policymakers are the steps that are needed to counter the problem of environmental degradation and provide a more promising future.